Baylisascaris procyonis Roundworm Seroprevalence among Wildlife Rehabilitators, United States and Canada, 2012–2015 - Sapp, Sarah G.H. (Emerg Infect Dis, 2016)
Baylisascaris procyonis roundworms can cause potentially fatal neural larva migrans in many species, including humans. However, the clinical spectrum of baylisascariasis is not completely understood. We tested 347 asymptomatic adult wildlife rehabilitators for B. procyonis antibodies; 24 were positive, suggesting that subclinical baylisascariasis is occurring among this population.